Effectiveness of Kenya National Examinations Council Measures in Curbing National Examination Malpractices in Public Secondary Schools in Kisii County (International Journal of Scientific Research and Management (IJSRM), 2016)
The study investigated how effectively the Kenya National Examination Council (KNEC) measures are implemented to curb examination malpractices in secondary schools in Kisii County. The population of the study consisted of 104,649 participants drawn from 237 public secondary schools in the County. Stratified and simple random sampling techniques were used to select a sample of 867 subjects who responded to the Examination malpractices, Examination measures and Attitude Questionnaire. Data collected was analyzed with ANOVA and Chi-square statistics. The key findings indicated that there is a relationship between examination malpractices and school category. Also, the malpractices begin at class level influencing the malpractices that occur during KCSE. The inferential statistics results were; x2 (12) = 0.035 p < 0.05, F (2,109) = 0.863 P < 0.05 and F (3, 108) = 6.298 p< 0.05 for hypothesis one, two and three respectively. In hypothesis one, the result indicated that there is a relationship between examination malpractices and school category. Hypothesis two implied that that the teachers’ attitudes towards KNEC measures for curbing examination malpractices depended on the type of school where the teacher worked while hypothesis three implied that examination malpractices in Kisii County were so much dependent on whether the school is national, county or sub county in terms of category. Therefore it was recommended that the education system should consider using the assessments carried out in school to contribute to a student’s final grade instead of emphasizing on the final examinations only.